2016
DOI: 10.1371/journal.pone.0160331
|View full text |Cite
|
Sign up to set email alerts
|

Differential Analysis of the Nasal Microbiome of Pig Carriers or Non-Carriers of Staphylococcus aureus

Abstract: Staphylococcus aureus is presently regarded as an emerging zoonotic agent due to the spread of specific methicillin-resistant S. aureus (MRSA) clones in pig farms. Studying the microbiota can be useful for the identification of bacteria that antagonize such opportunistic veterinary and zoonotic pathogen in animal carriers. The aim of this study was to determine whether the nasal microbiome of pig S. aureus carriers differs from that of non-carriers. The V3-V5 region of the 16S rRNA gene was sequenced from nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…aureus colonization in the nose [ 49 , 50 ]. In addition to the role for S. epidermidis and Dolosigranulum species, a role for Lachnospiraceae should be explored in S. aureus non-carrier phenotype as suggested by Espinosa-Gongora et al [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…aureus colonization in the nose [ 49 , 50 ]. In addition to the role for S. epidermidis and Dolosigranulum species, a role for Lachnospiraceae should be explored in S. aureus non-carrier phenotype as suggested by Espinosa-Gongora et al [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variations in the microbiota composition associated with both types of G. parasuis strains could be driven by the physiology of the different bacterial community, which could impact the magnitude of virulent or non-virulent strains colonization and prevalence, and subsequently, the piglet's health status [4]. In a similar infection study, Espinosa-Gongora et al [13] reported that nasal microbiome of pigs that are not colonized with Staphylococcus aureus harbors several species/taxa that are significantly less abundant in carrier pig, suggesting that the nasal microbiota plays a role in the individual predisposition to S. aureus nasal carriage in pigs. In the earlier study by Correa-Fiz et al [1], a marked difference between the composition and diversity of the nasal microbiota between swine farms with different health status was reported.…”
Section: Microbiota Associated With G Parasuis Of Different Virulencementioning
confidence: 99%
“…Several recent studies uncovered the nasal microbiota composition in pigs and their association with different infectious pathogens [1,[12][13][14]. Strube et al [14] showed that the porcine nasal mucosa harbored Rothia and had higher relative levels of Streptococcus and Moraxella, while levels of Aerococcus, Facklamia and Jeotgalibaca were relatively lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated the impact of the microbiota in S . aureus carriage in both pigs 21 and mice 22 .…”
Section: Introductionmentioning
confidence: 99%